2015
DOI: 10.3390/nu7085277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pre-Pregnancy Dietary Intake with a Food Frequency Questionnaire in Alberta Women

Abstract: Purpose: Pre-pregnancy is an under-examined and potentially important time to optimize dietary intake to support fetal growth and development as well as maternal health. The purpose of the study was to determine the extent to which dietary intake reported by non-pregnant women is similar to pre-pregnancy dietary intake reported by pregnant women using the same assessment tool. Methods: The self-administered, semi-quantitative food frequency questionnaire (FFQ) was adapted from the Canadian version of the Diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Participants were categorized as “high” probiotic consumers if they consumed on average greater than or equal to 1 billion CFU per day on average for the duration of the study. Probiotic supplementation and dietary intake was tracked throughout the study using a validated 24-hour recall questionnaire adapted from the Alberta Pregnancy Outcomes and Nutrition (APrON) cohort study 56 . We tracked illnesses from reported occurrence and duration of enteric and respiratory illness symptoms by caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were categorized as “high” probiotic consumers if they consumed on average greater than or equal to 1 billion CFU per day on average for the duration of the study. Probiotic supplementation and dietary intake was tracked throughout the study using a validated 24-hour recall questionnaire adapted from the Alberta Pregnancy Outcomes and Nutrition (APrON) cohort study 56 . We tracked illnesses from reported occurrence and duration of enteric and respiratory illness symptoms by caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…Diet prior to pregnancy was assessed by a Food Frequency Questionnaire (FFQ), based on the National Cancer Institute’s Diet History Questionnaire for Canadians [ 22 ], and has been validated for assessing pre-pregnancy diet [ 23 ]. The FFQ was completed by participants during their first study visit.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, previous research has suggested that health education around effective weight management can affect weight gain during pregnancy (Wilkinson et al, 2009), with further evidence to suggest that pre-conception interventions can improve both the intention and self-efficacy of healthy eating behaviours during pregnancy (Hillemeier et al, 2008). There is also emerging evidence to suggest that women start eating healthily in preparation for pregnancy (Ramage et al, 2015).…”
Section: Dietary Intake Change Before and During Pregnancymentioning
confidence: 99%